Iodine adsorption material and preparation method and application thereof
By preparing an iodine adsorption material with sulfur powder and stannous chloride as the main raw materials, the problems of high cost, small adsorption capacity and low environmental contact area of existing iodine adsorption materials are solved, and efficient and economical iodine adsorption is achieved. Effect.
Patent Information
- Application Number
- CN202411313765.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-20
AI Technical Summary
In industrial production applications, existing iodine adsorbent materials have problems such as high cost, small adsorption amount and low environmental contact area, and it is difficult to effectively remove gaseous radioactive iodine, resulting in pollution diffusion.
By dissolving sulfur powder in diethylenetriamine and then adding stannous chloride for heating reaction, an iodine adsorption material is prepared. The material is composed of a compound of sulfide and metallic tin and has high adsorption capacity and stability.
The iodine adsorption material has high adsorption capacity, low cost, mild preparation conditions, is suitable for large-scale production, can effectively reduce the risk of radioactive iodine contamination, and shows good performance in different scenarios.
Smart Images

Figure CN118847069B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid adsorbents, and in particular relates to an iodine adsorption material and a preparation method thereof, as well as application of the material in a radioactive iodine adsorption environment. Background Art
[0002] Nuclear energy is one of the clean energy sources with the greatest potential for human use. However, with the continuous development of nuclear power, the reserves of spent nuclear fuel are also increasing. Spent fuel contains unfissioned uranium-235, which needs to be recycled and reused. In this process (i.e., spent fuel reprocessing), a large amount of gaseous radioactive iodine will be produced. Compared with solid radioactive waste, gaseous radioactive iodine has the characteristics of high fluidity and easy migration, resulting in a larger pollution area and more likely to cause serious harm to the ecological environment and human health. The adsorption and treatment of gaseous iodine in the waste gas of the reprocessing plant has become an important research content in the treatment of radioactive waste gas. At present, people mainly use dry dust removal, liquid absorption and solid phase adsorption to remove radioactive iodine from the gas. Dry dust removal has low efficiency in treating radioactive gases and is mainly used for the disposal of radioactive aerosols. The liquid absorption method mainly includes mercury washing, acid washing and alkali washing. Although this method has a high absorption efficiency, it uses a large amount of toxic mercuric nitrate or strong acids and alkalis such as nitric acid and sodium hydroxide. The operation and maintenance costs of the equipment are high and it is easy to produce a large amount of radioactive waste liquid. Solid phase adsorption is one of the important methods for iodine removal. Potential solid phase adsorbents include silver-based zeolite, activated carbon, metal-organic framework materials, etc.
[0003] Silver-based zeolite mainly relies on active silver (Ag) loaded on a solid carrier as an adsorbent to convert radioactive iodine into solid AgI, thereby removing iodine. The biggest limitation of this adsorbent in practical applications is the instability of the Ag-I bond, which is easily broken by external conditions such as light and temperature, resulting in the re-release of radioactive iodine and causing radioactive pollution. The disadvantage of silver-based zeolite is that its raw material silver is a precious metal with high price, and the cost is difficult to control during large-scale production. Activated carbon (AC) is a traditional adsorption material composed of carbon with a porous structure. The traditional nuclear industry method to enhance the adsorption effect of activated carbon on iodine vapor is to impregnate organic amine (triethyldiamine) on activated carbon. However, its disadvantages are also obvious: organic amines are easy to sublime, and the iodine adsorption capacity of activated carbon decreases with increasing temperature; the adsorption of iodine by activated carbon is an exothermic process, and the presence of organic amines reduces the ignition point of the impregnated activated carbon, exacerbating potential safety hazards; the impregnated activated carbon is easily poisoned and inactivated, with poor regeneration ability, and it is difficult to reuse; the adsorbed iodine is easy to desorb. Metal-Organic Frameworks (MOFs) are porous crystalline materials formed by self-assembly of metal ions or clusters bridging organic ligands through coordination. As metal-organic framework materials, MOFs have excellent controllability and processability, and have great research and application prospects in enriching radioactive iodine. However, how to reduce the difficulty and cost of material synthesis and improve the adsorption performance of adsorbents and stability under extreme conditions are still major challenges faced by researchers.
[0004] In the nuclear industry, especially in high-risk environments such as nuclear power plants and nuclear fuel processing, the use of effective iodine protective equipment is essential to protect the health of workers and the public. At present, the iodine protective equipment commonly used in the nuclear industry mainly includes iodine adsorption filters, respiratory protective equipment, and personal protective equipment. Iodine adsorption filters are mainly used in purification devices of ventilation systems, and the core part is iodine adsorbents. The adsorbent efficiently adsorbs radioactive iodine in the air, thereby eliminating the harm of nuclear radiation to the human body. Respiratory protective equipment is mainly masks and filter cartridges, such as 3M's 60928CN filter cartridge and FR-57 filter canister, which have the function of filtering radioactive iodine. In addition to respiratory protective equipment, personal protective equipment also includes personal protective equipment such as protective clothing, protective gloves, and protective glasses. These supplies can effectively isolate radioactive substances from direct contact with the skin and reduce the risk of radioactive contamination. However, the above-mentioned iodine protective equipment all have the problems of high cost and small iodine adsorption. Summary of the invention
[0005] The purpose of the present invention is to provide an iodine adsorption material with high adsorption capacity, easy preparation, low cost and environmental friendliness to solve the problem that the contact area between the iodine adsorption material powder and the environment is not high in industrial production applications. At the same time, the present invention provides a preparation method of the iodine adsorption material and its application in different scenarios.
[0006] The iodine adsorption material provided by the present invention is prepared by the following method:
[0007] Step 1: Add sulfur powder to diethylenetriamine, heat and stir at 50-80°C until the sulfur powder is completely dissolved, cool to room temperature, add stannous chloride powder, stir and react at 90-150°C for 4-8 hours to obtain a slurry;
[0008] Step 2: Add methanol to the slurry obtained in step 1, stir thoroughly and filter, and dry the filter disc to obtain the iodine adsorption material.
[0009] In the above step 1, the mass ratio of the sulfur powder to diethylenetriamine is preferably 1:6-9.
[0010] In the above step 1, the mass ratio of the sulfur powder to the stannous chloride powder is preferably 1:1 to 2.2.
[0011] In the above step 1, it is further preferred to stir the reaction at 110 to 120° C. for 5 to 6 hours.
[0012] In the above step 2, the volume ratio of the slurry to methanol is preferably 1:1.5-4.
[0013] The present invention provides the use of the iodine adsorbent material in preparing an iodine adsorbent for a nuclear industry ventilation purification system, and the specific method is: the iodine adsorbent material is composite-molded with a polymer or an adhesive. When the iodine adsorbent material is composite-molded with a polymer, the iodine adsorbent material is uniformly dispersed in a polymer solution, a curing agent is added to form or directly added to a mold for cooling and forming, to obtain a composite pellet or composite film or composite particle, i.e., an iodine adsorbent; the polymer is any one of polyethersulfone, polyvinyl chloride, and polyethylene, and the curing agent is a mixed solution of anhydrous ethanol and water in a mass ratio of 1:0.8 to 1. When the iodine adsorbent material is composite-molded with an adhesive, the adhesive and the iodine adsorbent material are uniformly mixed, added to a mold for heating and forming, to obtain a composite pellet or composite particle, i.e., an iodine adsorbent; the adhesive is any one or more of a cellulose adhesive, a phosphate adhesive, and a phenolic resin.
[0014] The present invention also provides the use of the iodine adsorption material in the preparation of iodine respiratory protective masks. There are two preparation methods. One preparation method is: the iodine adsorption material is uniformly dispersed in a solvent, and a fiber structure material is added for impregnation and composite molding. The obtained molded fiber composite material is used to prepare an iodine respiratory protective mask; the solvent is any one of water, ethanol, and ethylene glycol; the fiber structure material is any one of wood fiber, cotton fiber, activated carbon fiber, chemical fiber, and glass fiber. Another preparation method is: the iodine adsorption material is uniformly dispersed in ultrapure water, and a porous structure material is added, and the reaction is heated at 120 to 140°C under closed conditions for 2 to 6 hours. The obtained molded porous composite material is used to prepare an iodine respiratory protective mask; the porous structure material is any one of activated carbon, foam plastic, ceramic material, and zeolite molecular sieve.
[0015] The present invention also provides the use of the iodine adsorption material in preparing the sealing material of nuclear industry equipment. The specific method is: the iodine adsorption material is evenly dispersed in an adhesive, directly cured and formed, and the obtained molded composite material is used as the sealing material of nuclear industry equipment; the adhesive is any one or more of silica gel, silicone resin, and epoxy resin.
[0016] The present invention also provides the use of the iodine adsorption material in preparing hand skin protection equipment. The specific method is: uniformly dispersing the iodine adsorption material in nitrile rubber latex to obtain a latex mixture; soaking a hand mold with a protective layer of gloves with a release agent, then soaking it with the latex mixture, and drying to obtain a finished iodine adsorption composite glove.
[0017] The beneficial effects of the present invention are as follows:
[0018] 1. The present invention dissolves sulfur powder in diethylenetriamine and then adds tin dichloride to heat and react to generate iodine adsorption material. Compared with other iodine adsorption products in the same field, the cost of raw materials used is greatly reduced, and it is widely available, which effectively reduces the production threshold.
[0019] 2. The preparation method of the iodine adsorption material of the present invention is easy to operate, the preparation conditions are mild and friendly, the harm to the human body and the environment during the preparation process is reduced, and a high yield can be achieved while ensuring production efficiency, and it has the potential for large-scale and industrialized production.
[0020] 3. The iodine adsorption material of the present invention has excellent performance in the field of iodine adsorption, and its adsorption capacity far exceeds similar products on the market. At the same time, because of its good adsorption stability, it can reduce the secondary environmental problems that may be caused by adsorbent desorption while meeting the iodine adsorption requirements of the nuclear industry. At the same time, in addition to the iodine purification device for the ventilation system, the molded product of the present invention also has great application prospects in the fields of iodine vapor respiratory protection, iodine vapor personal protection and sealing materials.
[0021] 4. The storage conditions of the iodine adsorption material of the present invention are mild and can be stored in a cool and dry place without providing more complicated storage conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the XRD spectrum of the iodine adsorption material prepared in Example 1.
[0023] Figure 2 is a SEM image of the iodine adsorption material prepared in Example 1.
[0024] Figure 3 This is an EDS electron image of the iodine adsorption material prepared in Example 1.
[0025] Figure 4 1 and 2 are distribution diagrams of some elements in the iodine adsorption material prepared in Example 1, wherein (a) is the O element distribution diagram, (b) is the S element distribution diagram, and (c) is the Sn element distribution diagram.
[0026] Figure 5 This is the EDS surface spectrum of the iodine adsorption material prepared in Example 1.
[0027] Figure 6 This is the iodine vapor adsorption curve of the iodine adsorption material prepared in Example 1.
[0028] Figure 7 This is a comparison chart of the static adsorption of iodine vapor by different molding materials. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but these embodiments should be understood as being only used to illustrate the present invention and not to limit the scope of protection of the present invention. After reading the contents recorded in the present invention, various changes or modifications made to the present invention based on the principles of the present invention also fall within the scope defined by the claims of the present invention.
[0030] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial channels unless otherwise specified. Example 1
[0031] Step 1: Take 600g of diethylenetriamine and heat it to 70°C, slowly add 77g of sulfur powder thereto, heat and stir at 70°C until the sulfur powder is completely dissolved, wait for it to cool to room temperature, slowly add 124g of stannous chloride powder to the resulting solution, and after all is added, heat and stir in an oil bath at 120°C for 6 hours to obtain a slurry.
[0032] Step 2: Take 50 mL of the slurry obtained in step 1, pour into 100 mL of methanol, stir thoroughly and filter, take the filter disc and dry it at 80°C to obtain a light yellow powder, i.e., the iodine adsorption material. Figure 1 It can be observed that the main phase in the material is tin sulfide, accompanied by free sulfur, and the overall structure has good long-range order. Figure 2 It can be seen that there are no obvious pores on the surface of the material, which indicates that the source of its high adsorption capacity for iodine is less related to physical adsorption and more due to chemical adsorption. Figures 3 to 5 It can be seen that the main elements in the material are S, Sn, and O. The element distribution is relatively uniform and S and Sn are the main elements. Figure 4 and Figure 5 Taken together, the O in the material may be due to the oxidation of a small amount of Sn or S during the preparation process.
[0033] The density of the iodine adsorbent obtained in this example is 1.42 g / cm 3 , the total pore volume is 0.113 cm 3 / g, average pore size is 3.825nm, specific surface area is 1.181m 2 / g. The test conditions for static adsorption are: prepare iodine vapor or iodomethane 0.5-1g, test sample loading 0.02-0.5g, saturated adsorption at 75°C for 48-60 hours, and the mass difference before and after is the saturated static adsorption amount. The test parameters for dynamic penetration are: set the carrier gas flux to 200cm 3 / min, iodine elemental flow rate 12mg / h, 0.3-1g test sample loaded, and the iodine concentration at the carrier gas outlet was monitored at 100℃. Figure 6 The results showed that the static adsorption capacity of iodine vapor of the iodine adsorption material obtained in this example was 6.74 g / g, the static adsorption capacity of methyl iodide was 0.65 g / g, the dynamic adsorption capacity of iodine vapor was 2.51 g / g, and the penetration time of 0.83g was 5.73 hours. Example 2
[0034] Step 1: Take 600g of diethylenetriamine and heat it to 80°C, slowly add 90g of sulfur powder thereto, heat and stir at 80°C until the sulfur powder is completely dissolved, wait for it to cool to room temperature, slowly add 110g of stannous chloride powder to the resulting solution, and after all is added, heat and stir in an oil bath at 120°C for 6 hours to obtain a slurry.
[0035] Step 2: Take 50 mL of the slurry obtained in step 1, pour into 100 mL of methanol, stir thoroughly and filter, take the filter disc and dry it at 80°C to obtain a light yellow powder, i.e., the iodine adsorption material. Example 3
[0036] Step 1: Take 600g of diethylenetriamine and heat it to 70°C, slowly add 77g of sulfur powder thereto, heat and stir at 70°C until the sulfur powder is completely dissolved, wait for it to cool to room temperature, slowly add 140g of stannous chloride powder to the resulting solution, and after all is added, heat and stir in an oil bath at 140°C for 4 hours to obtain a slurry.
[0037] Step 2: Take 50 mL of the slurry obtained in step 1, pour into 100 mL of methanol, stir thoroughly and filter, take the filter disc and dry it at 80°C to obtain a light yellow powder, i.e., the iodine adsorption material. Example 4
[0038] Take 150g of PES particles (polyethersulfone) and heat and dissolve them in 1000mL of DMF (N,N-dimethylformamide). After they are completely dissolved, add 9g of polyether P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer), stir and mix evenly, then slowly add 200g of iodine adsorption material prepared in Example 1 under heating and stirring conditions at 90°C, continue heating and stirring at 90°C for 1 hour after adding, and obtain a suspension without precipitation and large particle aggregation; use a mixed solution with a volume ratio of anhydrous ethanol and ultrapure water of 1:1 as a curing agent, slowly drip the obtained suspension into 1200mL of curing agent for curing and forming, and let the cured small balls stand in the curing agent for more than 24 hours, then remove and dry to obtain a formed composite small ball. The obtained formed composite small ball can be used as an iodine adsorbent in the ventilation and purification system of the nuclear industry. Example 5
[0039] In Example 4, the obtained suspension is applied to a clean glass surface with a scraper, and after it is naturally dried, it is carefully peeled off and stored to obtain a formed composite film. The obtained formed composite film can be used as an iodine adsorbent in an industrial ventilation purification system. Example 6
[0040] 16 g of the iodine adsorbent material prepared in Example 1 was put into a beaker, and 4 g of phenolic resin powder was added and stirred to mix evenly. Anhydrous ethanol was added to the beaker, and it was stirred to form a semi-paste mixture, which was poured into a mold, and the mold was shaken to remove air from the mixture. The mixture was dried in a blast oven at 80° C. for 4 hours to solidify it, and then it was taken out and demolded after cooling to room temperature to obtain a molded composite particle. The obtained molded composite particle can be used as an iodine adsorbent in a ventilation purification system of the nuclear industry. Example 7
[0041] In Example 6, 18 g of the iodine adsorption material prepared in Example 1 was taken into a beaker, and 2 g of phenolic resin powder was added and stirred to mix evenly. The other steps were the same as in Example 6. Example 8
[0042] The iodine adsorbent material prepared in Example 1 is uniformly dispersed in ultrapure water to obtain a 10 mg / mL iodine adsorbent dispersion; the non-woven fabric is cut into pieces, and is immersed in the 10 mg / mL iodine adsorbent dispersion for 20 minutes, and then taken out and dried; the above-mentioned immersion process is repeated 2 to 3 times, and a shaped composite non-woven fabric is obtained after drying. The obtained shaped composite non-woven fabric can be used as an iodine filter cloth in an iodine respiratory protective mask. Example 9
[0043] 0.6 g of the iodine adsorbent material prepared in Example 1 was evenly dispersed in 20 mL of ultrapure water, poured into a hydrothermal reactor, and 10 g of activated carbon was added thereto. After sealing, the mixture was heated at 120 ° C for 4 hours. After cooling to room temperature, the mixture was taken out and filtered, and the carbon material filtered was dried to obtain a shaped composite activated carbon. The shaped composite activated carbon obtained can be used as an iodine adsorbent in an iodine respiratory protective mask. Example 10
[0044] 5 g of the iodine adsorbent material prepared in Example 1 was added to 150 mL of silica gel, stirred and mixed evenly, the mixed silica gel fluid was poured into a mold, refrigerated for 30 minutes, taken out, baked at 80° C. for 2 hours, taken out and cooled to room temperature before demolding to obtain a molded composite silica gel. The obtained molded composite silica gel can be used as a sealing material in nuclear industry equipment. Embodiment 11
[0045] In Example 10, 10 g of the iodine adsorption material prepared in Example 1 was added to 150 mL of silica gel, and the other steps were the same as in Example 10. Example 12
[0046] 10 g of the iodine adsorbent material prepared in Example 1 was added to 200 mL of nitrile rubber latex and stirred for 1 hour to obtain a latex mixture. The hand model with the protective layer of the glove was immersed in a release agent (polycaprolactone solution), taken out and the excess release agent was gently shaken off, and then the hand model was immersed in the latex mixture, taken out and the excess latex mixture was gently shaken off, and placed in an oven to dry at 40° C. for 120 minutes to obtain a finished iodine adsorption composite glove.
[0047] Figure 7 It is the static adsorption amount of iodine vapor of different molding materials in the above-mentioned Examples 4, 5, 7, 9, and 10, wherein the original adsorption amount is the control group without adding iodine adsorbent material, and the adsorption amount is the adsorption amount of iodine adsorbent material per unit mass in the material. It can be observed from the figure that the iodine adsorption amount of all control groups is extremely small, and after adding iodine adsorbent material to prepare the molding, although different molding processes have differences, the effect on the adsorption performance of iodine adsorbent material is small, among which the performance of the molded composite particles of Example 7 decreases the least, and the iodine adsorption amount is 6.6937g / g, and the molded composite activated carbon of Example 9 is second, and the iodine adsorption amount is 6.6829g / g.
Claims
1. A method for preparing an iodine adsorbent material, characterized in that: The steps include: Step 1: adding sulfur powder to diethylenetriamine, heating and stirring at 50-80°C until the sulfur powder is completely dissolved, cooling to room temperature, and then adding stannous chloride powder, stirring and reacting at 110-140°C for 4-6 hours to obtain a slurry; wherein the mass ratio of the sulfur powder to diethylenetriamine is 1:6-9, and the mass ratio of the sulfur powder to stannous chloride powder is 1:1-2.2; Step 2: Add methanol to the slurry obtained in step 1, wherein the volume ratio of the slurry to methanol is 1:1.5-4, and filter after sufficient stirring. After the filter disc is dried, an iodine adsorption material is obtained; the main phase of the iodine adsorption material is metallic tin sulfide, accompanied by free sulfur.
2. The iodine adsorption material obtained by the preparation method according to claim 1.
3. An iodine adsorbent for use in a nuclear industry ventilation purification system, characterized in that: The iodine adsorbent is formed by compositely molding the iodine adsorbent material according to claim 2 and a polymer or an adhesive.
4. The iodine adsorbent for nuclear industry ventilation purification system according to claim 3, characterized in that: When the iodine adsorbent material is composited with a polymer, the iodine adsorbent material is uniformly dispersed in a polymer solution, and a curing agent is added to form the material or the material is directly added to a mold and cooled to form a composite pellet or a composite film or a composite particle, i.e., an iodine adsorbent. The polymer is any one of polyethersulfone, polyvinyl chloride, and polyethylene, and the curing agent is a mixed solution of anhydrous ethanol and water in a mass ratio of 1:0.8 to 1.
5. The iodine adsorbent for nuclear industry ventilation purification system according to claim 3, characterized in that: When the iodine adsorbent material is composite-formed with the adhesive, the adhesive and the iodine adsorbent are uniformly mixed, added into a mold and heated to form, so as to obtain composite pellets or composite particles, i.e., iodine adsorbent; the adhesive is any one or more of cellulose adhesive, phosphate adhesive, and phenolic resin.
6. Use of the iodine adsorption material according to claim 2 in the preparation of iodine respiratory protection equipment, wherein the iodine respiratory protection equipment is an iodine respiratory protection mask or a gas filter box.
7. Use of the iodine adsorbent material according to claim 6 in preparing iodine respiratory protection equipment, characterized in that: The iodine adsorption material is uniformly dispersed in a solvent, and a fiber structural material is added for impregnation and composite molding. The obtained molded fiber composite material is used as a filter layer material to prepare an iodine respiratory protective mask or a gas filter box; the solvent is any one of water, ethanol, and ethylene glycol; the fiber structural material is any one of wood fiber, cotton fiber, activated carbon fiber, chemical fiber, and glass fiber.
8. Use of the iodine adsorbent material according to claim 6 in preparing iodine respiratory protection equipment, characterized in that: The iodine adsorption material is uniformly dispersed in ultrapure water, and a porous structural material is added, and the reaction is heated at 120-140° C. under closed conditions for 2-6 hours. The obtained molded porous composite material is used as a filter layer material to prepare an iodine respiratory protective mask or a gas filter box; the porous structural material is any one of activated carbon, foam plastic, ceramic material, and zeolite molecular sieve.
9. A sealing material for nuclear industry equipment, characterized in that: The sealing material is formed by uniformly dispersing the iodine adsorption material described in claim 2 in an adhesive and directly curing the mixture.
10. The sealing material for nuclear industry equipment according to claim 9, characterized in that: The adhesive is any one or more of silica gel, silicone resin and epoxy resin.
11. Use of the iodine adsorption material according to claim 2 in preparing iodine protective equipment for hand skin.
12. Use of the iodine adsorbent material according to claim 11 in preparing iodine protective equipment for hand skin, characterized in that: The iodine adsorption material is uniformly dispersed in rubber latex to obtain a latex mixture; the hand mold with a protective layer of gloves is soaked with a release agent, then soaked with the latex mixture, and dried to obtain an iodine-absorbent composite glove, i.e., an iodine protective device for hand skin; the rubber latex is nitrile rubber latex or natural rubber latex.
Citation Information
Patent Citations
Two-dimensional chalcogenide and preparation method and application thereof
CN113896227A
Graphene quantum dot antibacterial and antiviral melt-blown cloth, mask and preparation method of graphene quantum dot antibacterial and antiviral melt-blown cloth
CN115142194A
Adsorbent for gaseous nox and sox
JP1995155586A